2021
DOI: 10.1007/s11250-021-02922-w
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility and nutritional composition of Leucaena leucocephala (Lam) leaf meal incorporated in the diets of Black Australorp and Potchefstroom Koekoek chicken breeds

Abstract: The objective of the study was to determine the apparent digestibility and nutrient composition of Leucaena leucocephala leaf meal (LLM) inclusion in Black Australorp and Potchefstroom Koekoek diets. Tender and mature leaves were separately harvested from 10 individual trees and stored separately for chemical analyses. The leaves were air-dried in a well-ventilated laboratory to constant weight and milled to pass through a 1-mm sieve. A mixture of tender and mature leaves was also collected to produce a bulk l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
3
2
0
Order By: Relevance
“…The results are in agreement with various reports of the proximate chemical composition of the other biosorbents, such as Leucaena leucocephala leaves [26,27] and Nostoc commune [28]. For example, if we compare our results with those reported for Leucaena leucocephala leaves, the ash content was higher than the 5.35% reported by Thamaga et al (2021) [26] but lower than the 6.62% reported by G.W. Garcia et al (2013) [27]; likewise, the protein contents were lower than 19.53% and 22.03% [26,27].…”
Section: Physicochemical Characterizationsupporting
confidence: 93%
See 2 more Smart Citations
“…The results are in agreement with various reports of the proximate chemical composition of the other biosorbents, such as Leucaena leucocephala leaves [26,27] and Nostoc commune [28]. For example, if we compare our results with those reported for Leucaena leucocephala leaves, the ash content was higher than the 5.35% reported by Thamaga et al (2021) [26] but lower than the 6.62% reported by G.W. Garcia et al (2013) [27]; likewise, the protein contents were lower than 19.53% and 22.03% [26,27].…”
Section: Physicochemical Characterizationsupporting
confidence: 93%
“…Table 1 presents the physicochemical parameters of A. compressa K. leaves in a sense to determine their nutritional composition. The results are in agreement with various reports of the proximate chemical composition of the other biosorbents, such as Leucaena leucocephala leaves [26,27] and Nostoc commune [28]. For example, if we compare our results with those reported for Leucaena leucocephala leaves, the ash content was higher than the 5.35% reported by Thamaga et al (2021) [26] but lower than the 6.62% reported by G.W.…”
Section: Physicochemical Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…Malik et al (2019) further reported that the seeds of L. leucocephala contain more fats than its leaves; however, the latter is richer in nutritional fats, especially polyunsaturated fatty acids, than saturated fatty acids. The crude fat present in Leucaena leaf meal was observed when Leucaena leaf meal was used in replacing a commercial broiler finisher diets in the diets of black australorp and potchefstroom koekoek chicken (Thamaga et al 2021). These authors reported an increase in the levels of crude fats in diets with Leucaena leaf meal compared with the control diet (0% Leucaena leaf meal).…”
Section: Discussionmentioning
confidence: 99%
“…The moderate ash level in the tested leaf meal shows that it is well endowed with minerals. The findings of Thamaga et al (2021) showed that Leucaena leaf meal is rich in essential minerals like copper, manganese, zinc and iron but contains a lesser amount of calcium, magnesium, potassium and sodium.…”
Section: Discussionmentioning
confidence: 99%